Pengaruh Limbah Plastik LDPE terhadap Karakteristik Lapisan Pengikat Beton Aspal (AC-BC) - Detha Sekar Langit Wahyu Gutama; Dewi Sulistyorini; Dimas Langga Chandra Galuh; Syaifullah M. Gorang (Universitas Sarjanawiyata Tamansiswa, 2026)
The increasing volume of plastic waste, particularly Low-Density Polyethylene (LDPE), has become a significant environmental challenge. In the context of sustainable infrastructure development, the utilization of LDPE waste as an additive in asphalt mixtures presents a potential solution. This study aims to evaluate the effect of LDPE addition on the Marshall characteristics of Asphalt Concrete-Binder Course (AC-BC) mixtures. An experimental method was conducted in the laboratory using LDPE content variations of 1.5%, 3%, 4.5%, 6%, and 7.5% by weight of asphalt, with a constant asphalt content of 5.5%. The tests included parameters such as bulk density, Voids in Mineral Aggregate (VMA), Voids in Mix (VIM), Voids Filled with Bitumen (VFB), stability, flow, and Marshall Quotient (MQ), following the Bina Marga 2018 Revision 2 standards. The results indicated that the addition of LDPE affected all Marshall characteristic parameters. At 1.5% LDPE content, the values obtained were a bulk density of 2.379 gr/cc, VMA of 15.49%, VIM of 4.15%, VFB of 77.28%, the highest stability of 1993 kg, flow of 3.07 mm, and a MQ of 650 kg/mm. LDPE content between 3% and 6% showed an increasing trend in VMA from 15.49% to 15.64% and in VIM from 4.15% to 4.32%, while VFB decreased to 72.38% at 6%. Flow values decreased from 3.27 mm at 3% LDPE to 2.67 mm at 7.5%. All parameters remained within the limits set by Bina Marga 2018 Revision 2 standards. This study demonstrates that LDPE can be utilized as an additive material in AC-BC mixtures, as it is capable of maintaining Marshall characteristics within the required technical standards.